Persistent benefit of pharmacogenomic testing on initial remission and response rates in patients with major depressive disorder - Hain, Daniel; Del Tredici, Andria L.; Griggs, Ryan B.; Law, Rebecca; Mabey, Brent; Johnson, Holly L.; Johansen Taber, Katherine; Lynch, Kevin G.; Gutin, Alexander; Oslin, David W. (Frontiers in Pharmacology, 2025)
BackgroundIn patients with major depressive disorder (MDD), achieving remission and/or response may take many months because of the lengthy trial-and-error process often needed to identify effective medication. Pharmacogenomic testing is a prescribing tool that has been shown to improve remission and response rates for MDD patients, but data describing its impact over time is limited. The objective of this study was to determine whether pharmacogenomic-guided treatment increases the rate of remission and response over time in patients with MDD, and if so, to assess the persistence of that effect.MethodsThis study was a prespecified post hoc analysis of the PRIME Care (Precision Medicine in Mental Healthcare) randomized clinical trial, a pragmatic trial that compared pharmacogenomic-guided treatment with usual care among veterans with depression. Participants were recruited at 22 Department of Veterans Affairs medical centers by 676 clinicians and were randomized to the pharmacogenomic-guided arm or the usual care arm. Multivariate Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for associations between study arm (pharmacogenomic-guided treatment or usual care) and the first instance of response or remission as assessed by the Patient Health Questionnaire-9 (PHQ-9) scale.Results1,764 (90.7%) of the 1,944 veterans who participated in the PRIME Care trial had sufficient visit data to be included in this analysis. Patients who received pharmacogenomic-guided treatment had higher rates of remission (HR [95% CI] = 1.27 [1.05, 1.53]; p = 0.015) and response (HR [95% CI] = 1.21 [1.05, 1.40]; p = 0.010) at any time relative to patients receiving usual care. Schoenfeld residuals tests were not statistically significant for remission (p = 0.931) or response (p = 0.112), providing no evidence that the benefit due to pharmacogenomic-guided treatment changed over the 24-week period.ConclusionPharmacogenomic-guided treatment led to faster initial remission and response in patients with MDD, and this benefit persisted over 6 months with no evidence of changing over time.